In defence of Modern Languages - Gerda Wielander (Modern Languages Open, 2014)
This article is a 3000 word long opinion piece/commentary in defence of Modern Languages as an academic discipline in its own right. it outlines some of the reasons why Modern Languages find themselves in a difficult position and argues that the future lies in cooperation, innovation and confident showcasing of Modern Languages research as exmplified by MLO.